Enhanced sulfur in the upper troposphere and lower stratosphere in spring 2020 - L. Tomsche; A. Marsing; T. Jurkat-Witschas; J. Lucke; S. Kaufmann; K. Kaiser; J. Schneider; M. Scheibe; H. Schlager; L. Röder; H. Fischer; F. Obersteiner; et al. (Atmospheric Chemistry and Physics, 2022)
Sulfur compounds in the upper troposphere and lower stratosphere (UTLS) impact the atmosphere radiation budget, either directly as particles or indirectly as precursor gas for new particle formation. In situ measurements in the UTLS are rare but are important to better understand the impact of the sulfur budget on climate. The BLUESKY mission in May and June 2020 explored an unprecedented situation. (1) The UTLS experienced extraordinary dry conditions in spring 2020 over Europe, in comparison to previous years, and (2) the first lockdown of the COVID-19 pandemic caused major emission reductions from industry, ground, and airborne transportation. With the two research aircraft HALO and Falcon , 20 flights were conducted over central Europe and the North Atlantic to investigate the atmospheric composition with respect to trace gases, aerosol, and clouds. Here, we focus on measurements of sulfur dioxide (SO 2 ) and particulate sulfate (SO <msubsup>42-</msubsup> <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="13pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="63f11f9b60a09208ebeae789905b238b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-15135-2022-ie00001.svg" width="13pt" height="17pt" src="acp-22-15135-2022-ie00001.png"/></svg:svg> ) in the altitude range of 8 to 14.5 km which show unexpectedly enhanced mixing ratios of SO 2 in the upper troposphere and of SO <msubsup>4<mn ...